2021
DOI: 10.1007/s11467-021-1080-y
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial fabrication of AgTe monolayer on Ag(111) and the sequential growth of Te film

Abstract: Transition-metal chalcogenides (TMCs) materials have attracted increasing interest both for fundamental research and industrial applications. Among all these materials, twodimensional (2D) compounds with honeycomb-like structure possess exotic electronic structures. Here, we report a systematic study of TMC monolayer AgTe fabricated by direct depositing Te on the surface of Ag(111) and annealing. Few intrinsic defects are observed and studied by scanning tunneling microscopy, indicating that there are two kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The results clearly revealed that the AgSe monolayer with a hexagonal lattice possesses two DNLFs protected by the inversion of the mirror symmetry when neglecting spin-orbit coupling (SOC). 26 In addition to the AgSe monolayer, Liu et al 27 and Dong et al 28 experimentally synthesized monolayer AgTe by tellurium (Te) deposition on the Ag(111) surface. Interestingly, angle-resolved photoemission supported by density functional theory (DFT) calculations have unequivocally confirmed that the AgTe layer is thermodynamically and chemically stable with a planar hexagonal structure and it possesses two DNLFs whose stability depends on the presence of the SOC effect.…”
mentioning
confidence: 99%
“…The results clearly revealed that the AgSe monolayer with a hexagonal lattice possesses two DNLFs protected by the inversion of the mirror symmetry when neglecting spin-orbit coupling (SOC). 26 In addition to the AgSe monolayer, Liu et al 27 and Dong et al 28 experimentally synthesized monolayer AgTe by tellurium (Te) deposition on the Ag(111) surface. Interestingly, angle-resolved photoemission supported by density functional theory (DFT) calculations have unequivocally confirmed that the AgTe layer is thermodynamically and chemically stable with a planar hexagonal structure and it possesses two DNLFs whose stability depends on the presence of the SOC effect.…”
mentioning
confidence: 99%